The Implementation of Hypnoteaching Method in Improving Students Reading Comprehension - Idham, Afif Zuhdy; Alam, Fiptar Abdi; Usman, Usman (Journal of Educational Sciences, 2025)
This study aims to determine the effectiveness of the Hypnoteaching method in improving the reading comprehension of second-grade students at SMA Modern IMMIM Putra Makassar, and identify which level of reading comprehension is most affected by this method, including literal, inferential, and critical comprehension. A quasi-experimental design was applied in this research. The participants were second-grade students of SMA IMMIM Putra Makassar, divided into two groups: an experimental group and a control group, each consisting of 30 students. Data were collected through reading comprehension tests. The results revealed that the mean posttest score of the experimental group 66.04 was higher than that of the control group 53.16. All three levels of reading comprehension improved significantly, as evidenced by the comparison of pretest and posttest mean scores. The largest improvement was observed in literal comprehension 87.66 > 44.00, followed by critical comprehension 59.66 > 54.00 and inferential comprehension 58.00 > 56.33. Based on these findings, it is concluded that the Hypnoteaching method is more effective than conventional teaching methods in improving the reading comprehension of second-grade students at SMA IMMIM Putra Makassar.